2020
DOI: 10.5398/tasj.2020.43.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms Related to Bovine Leptin Gene and Association with Productive and Reproductive Traits in Nellore Heifers

Abstract: The identification of genes and polymorphisms in female zebu related to the leptin gene that may be involved in better productive and reproductive performances is relevant to the livestock and economic sector. Thus, the objective of this study was to evaluate the SNP markers (T954M and C305T) and the BM1500 microsatellite and to analyze their associations with the traits of body weight, age at first calving (AFC), calving interval (CI), and reproductive efficiency (RE) in Nellore heifers. DNA extraction was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Considering other similar studies, the allele frequencies reported in the studies by Pomp et al (1997), Rasor et al (2002), Javanmard et al (2004), Leifers et al (2002, Javanmard et al (2005), Javanmard et al (2010), Kulig et al (2010), Öztabak et al (2010), Aytekin, (2011), Al-Janabi et al (2018), Ferchichi et al (2018, Maletic et al (2019), Kiyici et al (2019;Fernandes et al (2020) were similar to the allele frequencies in our study. According to the Hardy-Weinberg genetic equilibrium test performed for both breeds, LEP/Sau3AI gene polymorphism was in equilibrium in the Brown Swiss breed (X 2 =2.44; P>0.05), while it was not in equilibrium in the Simmental breed (X 2 =4.67; P<0.05).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Considering other similar studies, the allele frequencies reported in the studies by Pomp et al (1997), Rasor et al (2002), Javanmard et al (2004), Leifers et al (2002, Javanmard et al (2005), Javanmard et al (2010), Kulig et al (2010), Öztabak et al (2010), Aytekin, (2011), Al-Janabi et al (2018), Ferchichi et al (2018, Maletic et al (2019), Kiyici et al (2019;Fernandes et al (2020) were similar to the allele frequencies in our study. According to the Hardy-Weinberg genetic equilibrium test performed for both breeds, LEP/Sau3AI gene polymorphism was in equilibrium in the Brown Swiss breed (X 2 =2.44; P>0.05), while it was not in equilibrium in the Simmental breed (X 2 =4.67; P<0.05).…”
Section: Resultssupporting
confidence: 90%
“…There is an association between the leptin gene and single-nucleotide polymorphisms and numerous quantitative traits such as carcass fat, feed consumption, and milk yield (Kök et al, 2015;Al-Janabi et al, 2018;Kiyici et al, 2019). Polymorphisms in the leptin gene have been associated with milk performance (Liefers et al, 2002;Heravi et al, 2006;Kiyici et al, 2019), increased perinatal mortality in dairy products (Brickell et al, 2010), calf birth and weaning weights in beef and dairy products (Almeida et al, 2003;Nkrumah et al, 2005;DeVuyst et al, 2008;Fernandes et al, 2020), and reproductive traits in dairy cattle, such as gestational age (Komisarek and Antkowiak, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the nonsynonymous mutation of c.73T>C, the population of Madura cattle in VBC Waru was in Hardy-Weinberg equilibrium. A similar result was reported by Fernandes et al [35] in the Nellore cattle population. This equilibrium occurred when the Chi-square value was smaller than the Chisquare table [36].…”
Section: Discussionsupporting
confidence: 91%
“…Because the leptin gene is linked to productive and reproductive features both directly and indirectly, it's crucial to look into molecular markers that can look for connections with economically important traits [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Fernandes et al [ 32 ] revealed that, for the C305T SNP, there was a prevalence of the C allele (82%) over the T allele (0.18) and higher frequency for the CC genotype (0.67) in heifers. In a study with taurine breed, Buchanan et al [ 37 ] observed rates of 0.54 and 0.46 for the C and T alleles, respectively, and these authors also discovered a greater frequency for the C allele.…”
Section: Discussionmentioning
confidence: 99%